PIPELINE DEPTH ROUTE DESIGN WITH HORIZONTAL DIRECTIONAL DRILLING (HDD) UNDER THE KALIGARANG RIVER - Arviansyah, Yoga
Currently, the need for natural gas as energy source continues to increase. Therefore, distribution from production well is needed. The method for this distribution is using pipeline. Installation for pipeline of course has a variety of methods. One of the methods thath became the main highlight in this research is Horizontal Directional Drilling (HDD). This method is done by making hole in the ground then the pipe is pulled using HDD rig machine. The case study for this research is crossing the Kaligarang river in Semarang. The outputs of design process are determining suitable route for HDD, calculating stress, analyze pipe between LSAW and SSAW, and coating thickness. This research begin with calculating the theoretical load and stress. After that, Ansys is used to determine the stress that occurs in the pipe and coating. The resulting stress then compared with criterias for the HDD process during installation, operation, and hydrotest. There are two designs that can be selected from this case. It should be noted that these options arise as a result of two bending stress criterias. The stress that occurs in both options has met the specified criteria. The results of the calculation show that SSAW pipe can be selected. The coating thickness (PE) that can be propesed is 2.5 mm with minimum safety factor of 2.27.